Heterogeneous photocatalysis and its potential applications in water and wastewater treatment: a review - Ahmed, Syed Nabeel; Haider, Waseem (Nanotechnology, 2018)
There has been a considerable amount of research in the development of sustainable water treatment techniques capable of improving the quality of water. Unavailability of drinkable water is a crucial issue especially in regions where conventional drinking water treatment systems fail to eradicate aquatic pathogens, toxic metal ions and industrial waste. The research and development in this area have given rise to a new class of processes called advanced oxidation processes, particularly in the form of heterogeneous photocatalysis, which converts photon energy into chemical energy. Advances in nanotechnology have improved the ability to develop and specifically tailor the properties of photocatalytic materials used in this area. This paper discusses many of those photocatalytic nanomaterials, both metal-based and metal-free, which have been studied for water and waste water purification and treatment in recent years. It also discusses the design and performance of the recently studied photocatalytic reactors, along with the recent advancements in the visible-light photocatalysis. Additionally, the effects of the fundamental parameters such as temperature, pH, catalyst-loading and reaction time have also been reviewed. Moreover, different techniques that can increase the photocatalytic efficiency as well as recyclability have been systematically presented, followed by a discussion on the photocatalytic treatment of actual wastewater samples and the future challenges associated with it.